2013
DOI: 10.2105/ajph.2012.300944
|View full text |Cite
|
Sign up to set email alerts
|

Race/Ethnicity and the Relationship Between Homeownership and Health

Abstract: The mechanisms that create a significant association between homeownership and health seem not to be operative for racial/ethnic minorities or are countervailed by other processes, such as possible housing insecurity, that may create an adverse association. Homeownership provides a baseline for future investigations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 38 publications
0
23
0
Order By: Relevance
“…Previous research in this area has been so far mixed. Whereas a study using data from the Survey of Consumer Finances and the Health and Retirement Survey (both collected in 2004) found that wealth was associated with self-reported health among older Hispanic/Latinos (Pollack et al 2013), another study in California found that homeownership (a key measure of wealth) was not associated with self-reported health status, psychological health conditions, and general health conditions among Hispanic/Latinos (Ortiz and Zimmerman 2013). Yet another study, which included similar (albeit self-reported) outcome measures using data from the Panel Study of Income Dynamics, PSID, found that wealth was associated with obesity but not with hypertension (Hajat et al 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research in this area has been so far mixed. Whereas a study using data from the Survey of Consumer Finances and the Health and Retirement Survey (both collected in 2004) found that wealth was associated with self-reported health among older Hispanic/Latinos (Pollack et al 2013), another study in California found that homeownership (a key measure of wealth) was not associated with self-reported health status, psychological health conditions, and general health conditions among Hispanic/Latinos (Ortiz and Zimmerman 2013). Yet another study, which included similar (albeit self-reported) outcome measures using data from the Panel Study of Income Dynamics, PSID, found that wealth was associated with obesity but not with hypertension (Hajat et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…The latter may be particularly useful for racial/ethnic minorities whose wealth status, closely linked to homeownership, has been differentially impacted by the recent housing market crisis. Other researchers have pointed out the limitation of using such measures when they do not account for mortgage debt (Hajat et al 2010, Ortiz and Zimmerman 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Factors besides income and education, such as food security, housing, and neighborhood, can affect health. [13][14][15][16][17][18][19][20][21][22][31][32][33][34][35][36][37][38][39][40][41] For example, the work of Tarasuk et al 41 stresses food security as an important public health issue, describing food insecurity as a deprivation of a basic human need, which has lasting effects on an individual's health over the life course.…”
Section: Discussionmentioning
confidence: 99%
“…In order to be consistent with other studies that do not distinguish between mortgage status among owners, both of the ‘owned’ categories were combined into one category and compared with renters. [19, 20]…”
Section: Methodsmentioning
confidence: 99%